First record of Glabellula Bezzi (Diptera, Mythicomyiidae: Glabellulinae) in South America, with description of three new species from Brazil - Mendes, Luanna L.; Evenhuis, Neal L.; Limeira-De-Oliveira, Francisco; Lamas, Carlos J.e. (Zootaxa, 2022)
Studying material recently collected in Brazil, the authors found three new species of Glabellula (G. catiapatiuae sp. nov., G. rafaelae sp. nov., G. sarahae sp. nov.) that are described and illustrated herein. An identification key to the Brazilian species is also presented. This paper presents the first records of Glabellula in South America and the presence, for the first time, of the subfamily Glabellulinae in Brazil.